CONSTRUCTIVE PECULIARITIES OF THE INSTRUMENT FOR PRODUCTION OF SEAMLESS TUBE BILLETS - V. V. Klubovich; V. A. Tomilo; V. E. Ibragimov; O. N. Masutina (Литьë и металлургия)
In given article are described various types of sewing rollers, their advantages and defects, the characteristic of the is intense-deformed condition in the deformation center is resulted at an insertion on rollers various types are resulted. Besides, in article the directing tool sewing camps is described. The comparative characteristic of Disher’s disks and directing rulers is resulted.